Percepciones sobre la IRC y la adherencia a su tratamiento: visiones de pacientes, familiares y profesionales - Melo, Georgia (2024)
This paper was intended to analyze the perception of patients, relatives and professionals about Chronic kidney disease and treatment adherence. We conducted qualitative research with 47 participants who answered an interview script, whose data were analyzed in Iramuteq. The results showed that patients had little understanding about the disease and its treatment, as well as negative feelings associated with them. Among the factors that facilitate adherence, we highlight family/professional support; among the limiting factors, water restriction, diet, and limitations in the routine of the patient and caregiver. Professionals showed distinctions between hemodialysis and peritoneal dialysis, comparing limitations and benefits. We drew conclusions about the importance of paying attention to the factors that hinder treatment adherence to enhance its success.